The use of the Tapering in BPS Mesocycle by AZS AWF Wroclaw athletes - Kosendiak, Jan; Borkowski, Jacek; Hyjek, Katarzyna; Grobelna, Joanna; Gumienna, Róża (Journal of Education, Health and Sport, 2017)
Athletes, coaches, and sports academics are constantly working to maximize the, so called, sports form during the most important competitions. The form peak is usually achieved by decreasing the training load in the pre-scheduled period before the competition. This period of "cut-down" training is referred to as the tapering (or the taper). Tapering is a complex process affected by the number of factors, including volume, intensity, and frequency of training. If this process is successful, it is possible to achieve the peak form at the time of the major competitions. Tapering can thus become one of the most decisive factors in preparing an athlete for a competition. Aim of the paper and research questions. The research was undertaken under the grant RSA2 023 52 aimed at supporting the academic sport. The aim of the study was to identify the type and size of tapering used by coaches from the athletic section of KS AZS AWF Wroclaw in relation to top ranked athletes competing for the Academic World Championships, World and European Championships, and the Olympic Games. The utilitarian purpose was to develop recommendations for optimal tapering strategies. Method and test material The method of observation and measurement was applied. The training loads and responses to these loads during the direct competing preparation mesocycle (BPS) were recorded during the athlete's training cycle in 2014. The study involved two training groups coached by the TT and MR coaches from the athletic section of AZS AWF in Wrocław. The research material consisted of coaches' recordings, training diary entries, and records of training loads measurements performed during training units. These data were verified by lactate level and pulse rate measurements, which allowed controlling the selected physiological effects of training. The most important information from the study is that both coaches performed tapering only in the volume of training. In no case did the training frequency change. The structure of the 7-day microcycle was kept until the start day. No training unit had been canceled. Both coaches had never decreased the intensity of the means used, and they even motivated the athletes by measurements of the running time to increase the intensity, i.e. the speed for the running sections. Therefore, the tapering strategy adopted by the coaches did not concern either the frequency or the intensity of trainings, but only the volume of training measures used. Based on the results of the research and their analysis, the following conclusions can be formulated: 1. Trainers implement personal tapering programs. 2. In the analyzed cases, the tapering period amounted to approximately 16 days. 3. Tapering consisted in reducing the volume of workload to 30-60%, depending on the training unit type. 4. No workload intensity and training frequency have been decreased